THEORIES RELATED TO THE EMOTION OF ASTONISHMENT ТЕОРИИ, СВЯЗАННЫЕ С ЭМОЦИЕЙ УДИВЛЕНИЯ HAYRATLANISH HISSIYOTI BILAN BOG’LIQ NAZARIYALAR (International conference on multidisciplinary science, 2024)
this article discuses theories related to the emotion of astonishment and provides several notions from prominent scholars based on the topic.